Marketing as a business philosophy - Ziniak, O. R. (ТДАТУ, 2019)
Сonsidering marketing as a business philosophy requires an understanding of the democratic process of consumption, in which consumers have the right to “vote” for the product they need for their money. This determines the success of the company, which sets itself the task of studying the nature of needs and their fullest satisfaction.
Keywords: marketing; business; consumers